Impact of Iron Tablet and Moringa Leaf Capsule Supplementation on Hemoglobin Levels in Anemic Pregnant Women in Pariaman City, 2016 - Rissa, Maifah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Iron deficiency anemia is a prevalent global nutritional problem, particularly affecting pregnant women in developing countries. This study aimed to evaluate the effects of iron tablet supplementation and Moringa leaf capsules on hemoglobin (Hb) levels in anemic pregnant women in Pariaman City, Indonesia. Method: A total of 60 pregnant women were divided into two groups: one receiving iron tablets and the other Moringa leaf capsules for four weeks. Hemoglobin levels were measured before and after the intervention. Findings: In the iron supplementation group, the average Hb level increased from 9.05 g/dL to 9.46 g/dL, with a significant improvement (p = 0.001). Similarly, the Moringa capsule group showed an Hb increase from 8.99 g/dL to 9.27 g/dL (p = 0.019). While iron tablets resulted in a greater increase in Hb, Moringa capsules, rich in natural iron, also demonstrated significant effectiveness. The study concludes that both iron supplements and Moringa capsules are effective in increasing Hb levels, with Moringa capsules being a potential natural alternative for combating anemia in pregnant women. However, optimizing the dosage of Moringa could further enhance its efficacy. Factors such as adherence, diet, and knowledge of iron absorption enhancers and inhibitors play crucial roles in the success of the interventions.